Dynamics of hillocks formation during wet etching - Suarez, Maria Patricia (2008)
Etch hillocks formation was studied experimentally and modeled using the Monte Carlo method. Simulations were used to explore the consequences of site-dependent detachment probabilities on surface morphology for a one- and two-dimensional substrate models. Comparison with pyramidal etch hillocks that are regularly observed in anisotropic etching of Si(1 0 0) are presented. The steady-state morphologies are analyzed and the hillock size distributions determined. The mechanisms responsible for the steady-state morphologies are described.